Exploring Emilio Aguinaldo College Nursing Graduate Outcomes: A Longitudinal Study - Ranada, Joan O.; Remirez, Sheryl H.; Mendoza, Cherylline V.; Ortuoste, Ariel M.; Bataan, Reynalyn M.; Austria, Jayson S.; Watiwat, Kiana Coleen P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The tracer study sheds light on the importance of feedback from nurs-ing alumni about various aspects of their post-graduation experience. Its main purpose is to assess the effectiveness and relevance of the educational programs provided. The study typically collects infor-mation on employment status, job satisfaction, skills acquired, and the relevance of these skills to the labor market. Strengthening the relationship between the school and the alumni fosters networking opportunities, mentorship, and contributions to the Marian School of Nursing. The study specifically aimed to explore career placement and progression. A quantitative descriptive approach was used to analyze survey responses from 201 alumni nurses who graduated between 1992 and 2023. Online surveys were administered to alumni via Google forms. Descriptive statistics were utilized to analyze re-spondents' feedback. Results revealed that the majority have re-mained to work in the Philippines at 72% while a few Emilian nurses have chosen to work in the United States of America at 8.9%. Seven-teen percent (17%) of the respondents diverted to other career pathways or non-nursing jobs, with a predominance of Nursing grad-uates settling with their chosen career (83%). Based on the respond-ents' viewpoint, they have expressed deep gratitude towards their alma mater. Mostly have praised EAC for the gained excellent educa-tional experience and precious memories they have had during col-lege days. These are consistent achievements of the program goals and outcomes where alumni are expected to live a life of Virtue, Ex-cellence and Service. However, the study's findings suggest that our nursing leaders in academia and practice should make a firm com-mitment to working together to promote high-quality nursing prac-tice as well as high-quality nursing education. Global nursing leaders have the power to educate not only the next generation of nurses but also the public, including policymakers in both public and private in-stitutions. This is particularly true when it comes to enacting perti-nent laws that will help produce high-caliber nurses for both nursing practice and nursing education.